2017
DOI: 10.1007/jhep10(2017)150
|View full text |Cite
|
Sign up to set email alerts
|

Perturbative contributions to Wilson loops in twisted lattice boxes and reduced models

Abstract: Abstract:We compute the perturbative expression of Wilson loops up to order g 4 for SU(N ) lattice gauge theories with Wilson action on a finite box with twisted boundary conditions. Our formulas are valid for any dimension and any irreducible twist. They contain as a special case that of the 4-dimensional Twisted Eguchi-Kawai model for a symmetric twist with flux k. Our results allow us to analyze the finite volume corrections as a function of the flux. In particular, one can quantify the approach to volume i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Although our new condition has been obtained for the 2+1 dimensional system it might also affect the 4 dimensional case, but replacing N by √ N . Indeed, it can be shown that the value of Z min controls the size of the contribution of non-planar diagrams in perturbation theory [40]. However, if that also affects the existence of symmetry-breaking phase transitions in the non-perturbative region of the 3+1 system would only show up for N = 44 2 = 1936 or higher, which is hard to check.…”
Section: Conditions On the Flux For The Absence Of Phase Transitionsmentioning
confidence: 99%
“…Although our new condition has been obtained for the 2+1 dimensional system it might also affect the 4 dimensional case, but replacing N by √ N . Indeed, it can be shown that the value of Z min controls the size of the contribution of non-planar diagrams in perturbation theory [40]. However, if that also affects the existence of symmetry-breaking phase transitions in the non-perturbative region of the 3+1 system would only show up for N = 44 2 = 1936 or higher, which is hard to check.…”
Section: Conditions On the Flux For The Absence Of Phase Transitionsmentioning
confidence: 99%
“…The general procedure is similar to the infinite volume one in [3], though the computations and regularisation procedure turn out to be quite different. We first rescale the gauge fields in the Lagrangian, A µ (x) → g 0 A µ (x), and determine the Feynman rules in momentum space, which are essentially the usual ones replacing the group structure constants with F(p, q, −p − q); see for instance [18] and [19] for an analogous perturbative computation on the lattice. We then expand the flowed fields in powers of the bare coupling:…”
Section: Lo and Nlo Terms In Perturbation Theorymentioning
confidence: 99%
“…While we have chosen these two particular examples for illustration purposes, the appearance of spikes is a general phenomenon that we observe for orders approximately ≥ 30 on the volumes under study. is volume independent [48]. The infinite-volume value of p 1 can be obtained adding to the pure gauge contribution [49],…”
Section: Determination Of the P Nmentioning
confidence: 99%
“…Recently, the computation of Wilson loops has been treated in detail in Ref. [48]. Here we focus on two vertices, introducing Wilson and staggered fermions with smell in the fundamental representation.…”
Section: A Group Theory Conventionsmentioning
confidence: 99%